Transducers guide thermocouple measurements - Grozescu, Ionel Valeriu (Universiti Putra Malaysia Press, 2002)
Thermocouple measurements is intended to be a study guide for the physics and engineering students interested in experimental work involving temperature measurements using thermocouple. Besides the theoretical fundamentals of the thermocouple circuits such as Thomson, Peltier and Seeback effects, the book contains an extensive description of the practical aspects the reader may encounter during their experiments.